Penerapan Metode Ghina’ dalam Meningkatkan Kosa Kata Bahasa Arab pada Siswa Kelas IV SD. Islam Insan Terpadu - shobirin; Ahmadi; Isnol Khotimah; Nurhotimah (Mu'allim, 2022)
Inappropriate learning methods are often the cause of the failure of the Arabic language. Therefore we need a fun singing method. This study aims to describe the increase in Arabic vocabulary (mufrodat) with a singing model and measure how much effectiveness it is used. in this study the methods used by researchers are qualitative and quantitative research methods. Qualitative methods are used to describe the process in detail during the research using observation, interviews, and documentation techniques. As for the quantitative research method used to measure the effectiveness in its use using a questionnaire or questionnaire and data analysis using descriptive data analysis. The results of this study before the students used the singing method the average result was very low, namely 57.75%, while after using this method the average increased to 86.25%. So, the increase in vocabulary (mufrodat) with the singing model is said to be effective and successful, this can be seen from the learning outcomes which were initially sluggish & low but after the singing method was applied, the students' vocabulary mastery (mufrodat) increased. In addition, the response of students to the singing method in learning vocabulary (mufrodat) increased by 91%. So the singing method is able to foster a spirit of learning & mastery of Arabic vocabulary (mufrodat).